2011
DOI: 10.1524/ract.2011.1871
|View full text |Cite
|
Sign up to set email alerts
|

In vivo 212Pb/212Bi generator using indium-DTPA-tagged liposomes

Abstract: Indium-DTPA-tagged liposomes were studied in the present work as carriers of in vivo 212Pb/ 212Bi generator to be used in targeted alpha therapy. The liposomal uptake of 212Pb, into preformed liposomes, was investigated using different lipophilic chelate (DCP, 2,3-dimercapto-1-propanol (BAL), sodium acetate, and A23187), as a function of various parameters (temperature, concentrations of lipids, Pb, DTPA, ...) with 212Pb as a tracer. Different formulations of liposomes were tested to evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Besides organic ligands, other carriers, such as liposomes [87] and fullerenes [34], were also considered. Such kinds of transporters can provide the absence of release of daughter radionuclides after alpha decay due to recoil.…”
Section: Ligands and Other Carriers For Pb 2+mentioning
confidence: 99%
“…Besides organic ligands, other carriers, such as liposomes [87] and fullerenes [34], were also considered. Such kinds of transporters can provide the absence of release of daughter radionuclides after alpha decay due to recoil.…”
Section: Ligands and Other Carriers For Pb 2+mentioning
confidence: 99%
“…There also investigations where carbon nanomaterials have been proposed for 225 Ac, 223 Ra, and 211 At radionuclides [ 89 , 91 , 92 , 102 , 105 ]. Gold nanoparticles conjugated to 211 At [ 105 , 106 ], liposomes with 212 Pb/ 212 Bi [ 107 , 108 ], and hydroxyapatite nanoparticles [ 109 ] for retention of 212 Pb have been proposed with limited success.…”
Section: Nanoradiopharmaceuticals Based On Alpha Emittersmentioning
confidence: 99%
“…Montafon et al incorporated 212 Pb into indium-DTPA-tagged liposomes [98]. They found that the origin of the encapsulation is related to the dynamics of the surface, which makes the membrane partially permeable.…”
Section: Lead-212mentioning
confidence: 99%